2020
DOI: 10.3390/ijerph17041410
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of Land Consolidation Projects in Different Modes: A Case Study in Jianghan Plain of Hubei Province, China

Abstract: Land consolidation is essential in China for improving land use efficiency and supporting rural public space governance. Previously, the implementation of land consolidation projects (LCPs) had been mainly led by governments in China. In recent years, the Chinese government vigorously promoted land consolidation, and land consolidation in the corporation-leading mode (CLM) has emerged. This study focused on investigating the performance of CLM projects and the difference in performance levels between the CLM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Yang et al indicated that land remediation is an important measure to improve land-use efficiency and support land use. For improving the performance level of land remediation projects, policymakers should actively innovate land remediation implementation models and encourage agricultural enterprises to participate in land remediation activities [ 29 ]. Meanwhile, the focus of researchers in different regions differs.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al indicated that land remediation is an important measure to improve land-use efficiency and support land use. For improving the performance level of land remediation projects, policymakers should actively innovate land remediation implementation models and encourage agricultural enterprises to participate in land remediation activities [ 29 ]. Meanwhile, the focus of researchers in different regions differs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on rural geography and land use have pointed out that physical geographical conditions are the basic elements that determine the spatial distribution of different types of land use, and they further impact the quantitative structure and spatial layout of land resources [11,53]. Meanwhile, rural population, socioeconomic development and industrial structures may lead to changes of land-use pattern and functions in rural areas [10,54,55]. In addition, urban-rural relations can impact the rural land-use structure to some extent [56].…”
Section: Geodetector Modelmentioning
confidence: 99%
“…CLR essentially limits the right to development in a region, which forces the need for high-quality economic development through the optimization of land development rights. Previous studies on CLR have mainly focused on the impact of CLR on towns and villages [4], location choice [2], policy framework or mechanism of life cycle management of industrial land in China [9], and performance evaluation of land consolidation project [10]. It can be found that the studies on CLR mainly focus on the economic and social impact aspects of CLR, and there are fewer studies on the slow development of regions with net reduction of construction land.…”
Section: Introductionmentioning
confidence: 99%